Application of microencapsulated essential oils in cosmetic and personal health care products - a review - Ana Carvalho (2016)
Nowadays, the consumers around the world are increasingly focused on health and beauty. The renewed consumer interest in natural cosmetic products creates the demand for new products and reformulated others with botanical and functional ingredients. In cosmetic products, essential oils (EOs) play a major role as fragrance ingredients. They can optimize its proprieties and preservation, as well as the marketing image of the final product. Microencapsulation of EOs can protect and prevent the loss of volatile aromatic ingredients and improve the controlled release and stability of this core materials. The importance of EOs for cosmetic industry and its microencapsulation was reviewed in this study. Also a briefly introduction about the preparation of microparticles was presented. Some of the most important and usual microencapsulation techniques of EOs, as well as the conventional encapsulating agents, were discussed. Despite the fact that microencapsulation of EOs is a very promising and extremely attractive application area for cosmetic industry, further basic research needs to be carried out, for a better understanding of the biofunctional activities of microencapsulated EOs and its release modulation, as well as the effects of others cosmetic ingredients and the storage time in the microparticles properties.